(untitled) (Journal of Educational Sciences, 2016)
The article focuses on economics of quality of education, tendencies of development of organizational and economic mechanisms of educational management at the present stage are analyzed, possibilities for increase of effi ciency of activity of higher education institutions are determined, concept of management by expenses for quality is considered.